Evaluation of differences in performance between shareholder-CEO-led and professional-CEO-led large companies in Lithuania - Voveris, Donatas (Business: Theory and Practice, 2023)
There is an ongoing debate on what exactly are the differences between founder/shareholder-CEOs and professional-CEOs, and how those differences impact the performance of companies both from a managerial and financial standpoint. Though this issue attracted a lot of attention from scholars during the last 30 years, and the consensus has formed that there are indeed differences in motivational factors, managerial capabilities as well as risk-taking decisions between founder/shareholder-CEOs and professional-CEOs, the research on how this impacts firm performance provides inconsistent results. This paper aims to add to existing research in the field by evaluating whether there are significant differences in revenue growth rates and profitability between founder/shareholder-CEO-led and professional-CEO-led companies. Based on the revenue and profit data for the 5-year period of 2016 to 2020 of a sample of 205 of the largest companies in Lithuania, no significant differences in performance were identified. In this sense, this study confirms the generalization that the influence of a CEO diminishes as ventures grow and mature.